Analisis Kerusakan Jalan Metode Surface Distress Index (SDI) Pada Ruas Jalan Taman Karya Kota Pekanbaru - Belwa Putri, Wegia; Shalahuddin, Muhammad; 'Audah, Safridatul; Gussyafri, Haji (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2024)
Road damage is something that must be addressed immediately because it can hamper population mobility and other social activities that cross the Taman Karya road in Pekanbaru city, which has a road length of around 1,800 meters and a road width of 6 meters. This research aims to identify the types of damage on Jalan Taman Karya Pekanbaru City along STA 0+000 to STA 1+800 and determine the value of the condition of the road pavement using the Surface Distress Index (SDI) method. The results of the research obtained an analysis of the type of damage that occurred on Jalan Taman Karya Pekanbaru City STA 0+000 to STA 1+800, based on the SDI method there were 4 elements of damage, namely the crack area of ​​41.91%, with a crack width of 242.2 mm, the number of hole damage was 129 , and the average rut depth is 39.9 mm. The results of SDI calculations show that the road conditions on the Taman Karya road are still in good condition.